?2-Coordination of Chlorobenzenes to Rhenium Fragment Cp*Re(Co)2: Chemical and Photochemical Syntheses of Cp*Re(Co)2(?2-C6h6-Ncl N) - Godoy-Gonzalez, F; Godoy-Gonzalez, F (2011)
The complexes Cp*Re(CO)2(?2-C 6H6-nCln), n = 4, (5,6-?2-1,2,3, 4-C6H2Cl4) 2a; n = 3, (5,6-?2-1, 2,4-C6H3Cl3) 2b; n = 2, (2,3-?2- 1,4-C6H4Cl2) 2c and (4,5-?2-1,3- C6H4Cl2) 2d, have been conveniently prepared by two alternative procedures: Directly, by the photochemical reaction of Cp*Re(CO) 2 (N2) in neat or saturated hexane solution of the corresponding partially chlorinated benzene or stepwise, by the reaction of the appropriate trans-Cp*Re(CO) 2 (Ar Cl)X, X = Cl, Br (1a-d) with LiBHEt3 followed by protonation with HCl to form the hydrido complexes trans-Cp*Re(CO) 2 (Ar Cl)H which resulted thermally unstable in solution and convert to ?2-coordination complexes 2a-d. Due to their low stability as solids and in solution, the new complexes were only characterized by IR and 1H and 13C NMR spectroscopy. The 1H NMR spectra of the two derivatives containing dichlorobenzene (2c and 2d) indicate that a rapid exchange occurs between the hydrogen atoms on the coordinated carbons and those on the non-coordinated carbons.